MGluR-mediated calcium signalling in the thalamic reticular nucleus. Issue 6 (June 2016) - Neyer, Christina; Herr, David; Kohmann, Denise; Budde, Thomas; Pape, Hans-Christian; Coulon, Philippe
Graphical abstract: Highlights: For thefirst time, an IP3 -dependent release mechanism in TRN neurons is shown, which is triggered by mGluR-activation. Ca 2+ -release activates a flufenamic acid sensitive current with a reversal potential around −40 mV, suggesting an involvement of the Ca 2+ -activated nonselective cation conductance, ICAN . mGluR-mediated Ca 2+ -signalling in the TRN may allow differential modulation of thalamocortical activity via cortical inputs to the TRN. Abstract: The thalamic reticular nucleus (TRN) plays a major role in modulating the transfer of information from the thalamus to the cortex. GABAergic inhibition via the TRN is differentially regulated by metabotropic glutamate receptors (mGluRs) and the effect of mGluRs on the membrane potential, on ion channels, and on the plasticity of electrical coupling of TRN neurons has been studied previously. Although mGluRs are generally known to trigger Ca 2+ transients, mGluR-mediated Ca 2+ -transients in TRN neurons have not yet been investigated. In this study, we show that mGluRs can trigger Ca 2+ -transients in TRN neurons, that these transients depend on intracellular Ca 2+ -stores, and are mediated by IP3 receptors. Ca 2+ transients caused by the group I mGluR agonist DHPG elicit a current that is sensitive to flufenamic acid and has a reversal potential around −40 mV. Our results add mGluR-mediated Ca 2+ -signalling in the TRN to the state-dependent modulators of the thalamocortical system.